Cyber Security Department of Innovative Knowledge Institute (Paris Graduate School), Paris, France. (Global Journals of Research in Engineering, 2024)
Cybersecurity in Programmable Logic Controllers PLCs is a critical component in ensuring the overall security and reliability of industrial control systems PLCs are widely used in various industries to automate processes and control machinery However as PLCs become more interconnected with other systems and the internet they are increasingly vulnerable to cyber threats This abstract explores the importance of cybersecurity in PLCs and the potential risks associated with inadequate security measures It highlights the various ways in which PLCs can be compromised such as through malware attacks unauthorized access or physical tampering This abstract discusses the potential consequences of a cyber-attack on PLCs including disruption of critical infrastructure loss of sensitive data and potential harm to personnel It also emphasizes the importance of implementing robust cybersecurity measures such as encryption access control and regular security audits to protect PLCs from cyber threats Finally this abstract underscores the importance of prioritizing cybersecurity in PLCs to ensure the continued safety and reliability of industrial processes Failure to adequately secure PLCs can have far-reaching consequences making it imperative for organizations to invest in cybersecurity measures to safeguard their critical infrastructure
Keywords: IoT; cybersecurity; beretas; vulnerabilities; hacking; industry 40; threats; critical infrastructure